Acute nitrite exposure alters the metabolism of thyroid hormones in grass carp (Ctenopharyngodon idellus). (November 2017) - Xiao, Chen; Liu, Zidong; Li, Dapeng; Refaey, Mohamed M.; Tang, Rong; Li, Li; Zhang, Xi
Abstract: Nitrite has the potential to disturb thyroid hormone homeostasis, but little is known about the underlying mechanisms. In the present study, juvenile grass carp ( Ctenopharyngodon idellus ) were exposed to various concentrations of nitrite (0, 0.5, 1, 4, and 16 mg/L, respectively). Serum concentrations of triiodothyronine (T3 ), thyroxine (T4 ), free triiodothyronine (FT3 ), free thyroxine (FT4 ), 3, 3, 5ʹ-triiodothyronine (rT3 ), thyroid-stimulating hormone (TSH), and the activity of iodothyronine deiodinases were assayed at 0, 12, 24, 48, and 96 h after exposure. It was found that acute nitrite exposure significantly altered the TH levels and iodothyronine deiodinase activities. The rT3 levels were significantly increased in the treatment groups, whereas the concentrations of T3, FT3, FT4, and TSH decreased significantly. The concentration of T4 was elevated in the lower-dose exposure group, but was reduced in the higher-dose exposure group. Increases in type I iodothyronine deiodinase (ID1) and type III iodothyronine deiodinase (ID3) activities were observed in the exposure groups. The activity of type II iodothyronine deiodinase (ID2) decreased at 12 and 24 h after exposure. A decrease of colloid in the thyroid follicles was observed in the exposure group. The results indicate that acute nitrite exposure has the potential to disturb the homeostasis of thyroid hormone metabolism, leading to a hypothyroidism state in the juvenile grass carp. Highlights: Acute nitrite exposure alters iodothyronine deiodinase activities of grass carp. Acute nitrite exposure destroys homeostasis of thyroid hormones in grass carp. High dose of nitrite leads to decline in collide size of thyroid follicles in fish.